Jurisprudential Qualification for the joint-stock Company its Legality in Islamic Jurisprudence - Alsarahen, Hussien Hlayyel Suleiman (Journal of Islamic Sciences, 2021)
This study discusses the joint-stock company issue regarding its definition, its regulations, its qualification, and its legality in Islamic jurisprudence. This research is distinguished from other studies that shed the light on the same issue by dealing with the jurisprudential qualification for the joint-stock company, its legality, and the different opinions of the jurisprudents regarding its legality and discussing the legality proofs Then, the research explains which opinion outweighs others. the paper also explains both the jurisprudential and legal definitions of the joint-stock company and its regulations. The conclusion of the study includes results and recommendations.